2018
DOI: 10.1149/2.0151804jss
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ZnO and Heat Treatment Process on the Physical and Optical Properties of MgO-Al2O3-SiO2Glass-Ceramics

Abstract: The influences of adding ZnO and the use of specific heat-treatment schedules on MgO-Al 2 O 3 -SiO 2 (MAS) glass-ceramic properties including crystallization, micromorphology, optical transmittance and Vickers-hardness were investigated. The XRD analysis proved that MgAl 2 O 4 and Al 2 ZnO 4 spinel are the major crystalline phases formed in the studied MgO-Al 2 O 3 -SiO 2 -ZnO (MASZ) glass ceramics. The addition of ZnO facilitated the crystallization of the MAS glass and resulted in a uniform and compact micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Hu et al discussed the influence of ZnO and heat treatments on the MAS glass-ceramics and found that the addition of ZnO could promote crystallisation and improve the microstructure. Further, the crystallisation and nucleation time affect the Vickers hardness of the glass-ceramics [27]. He et al investigated the influence of different nucleating agents (TiO 2 , ZrO 2 and TiO 2 + ZrO 2 ) on the crystallisation and properties of the MAS glass-ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al discussed the influence of ZnO and heat treatments on the MAS glass-ceramics and found that the addition of ZnO could promote crystallisation and improve the microstructure. Further, the crystallisation and nucleation time affect the Vickers hardness of the glass-ceramics [27]. He et al investigated the influence of different nucleating agents (TiO 2 , ZrO 2 and TiO 2 + ZrO 2 ) on the crystallisation and properties of the MAS glass-ceramics.…”
Section: Introductionmentioning
confidence: 99%